Syekh Nawawi al-Bantani’s Thought on Adab Toward Others and Its Relevance in Contemporary Islamic Education - Melinda Cahyani Ningkrat Melinda; Aniqoh Aniqoh (EDUJAVARE: International Journal of Educational Research, 2026)
The thoughts of Sheikh Nawawi al-Bantani are an important part of the Islamic tradition in Indonesia. The objectives of this study are 1) To analyze the thoughts of Sheikh Nawawi al-Bantani in Maraqi al-Ubudiyah about the etiquette of fellow creatures understood and explained in his classical literature; 2) To analyze the concept of etiquette of fellow creatures in Maraqi al-Ubudiyah relevant to Islamic education in the contemporary era; 3) To analyze aspects of etiquette of fellow creatures that need to be prioritized in the implementation of the contemporary Islamic education curriculum based on Nawawi's thoughts; 4) To analyze the comparison of nuances between etiquette towards fellow creatures and etiquette towards God in Maraqi al-Ubudiyah, as well as its implications for the design of modern moral education programs. This research method uses qualitative with a library research approach (literature study) which is a data collection method that focuses on in-depth analysis of written texts, both published and unpublished. Data analysis in qualitative library research generally uses content analysis or critical discourse analysis methods. The results of the research are: 1) Adab towards fellow creatures through three main paths: (a) the basis of hadith in his commentary on Ghazali, (b) the construction of Sufi maqâmât which gave birth to social ethics, and (c) the relevance of classical literature to the practice of adab in the Islamic boarding school environment of the archipelago; 2) Adab towards fellow creatures in Maraqi al-Ubudiyyah can be operated in the context of contemporary Islamic education, by referring to relevant literature on adab, ta’dib, maqasid, and the integration of knowledge with morals; 3) Imam Nawawi and contemporary studies related to adab, teacher-student ethics, and social relations in the context of Islamic education, the priority of adab towards fellow creatures in the implementation of the contemporary curriculum needs to place adab teacher-student as the main foundation, followed by adab students, family adab, and school environment adab; 4) The book Maraqi al-‘Ubudiyah offers a complementary two-value framework between adab towards God and adab towards fellow creatures.